Preventing peri-implantitis: strategies, mechanisms, and clinical perspectives for inhibiting biofilm formation on implant surface - Zhou, Ziqian; Gu, Chunning; Guo, Li; Shi, Anyuan; Jing, Junyan; Cheng, Wei (Frontiers in Materials, 2026)
Next-generation antibacterial implant surfaces are rapidly evolving toward intelligent, adaptive, and patient-specific designs powered by emerging technologies such as smart biointerfaces, artificial intelligence–guided material optimization, and additive manufacturing. These advances promise to fundamentally reshape strategies for preventing peri-implant infections. However, their clinical translation remains constrained by critical challenges including activation thresholds of stimuli-responsive coatings, durability of anti-adhesion layers, long-term stability after release depletion, and the persistent “race for the surface” between bacteria and host tissue. Peri-implantitis, driven predominantly by bacterial adhesion and biofilm maturation on implant surfaces, continues to compromise the longevity of dental and orthopedic implants, and conventional mechanical or antibiotic-based therapies often fail to fully eradicate resilient biofilms. Recent progress in antibacterial implant surface engineering is summarized in this review, covering two complementary strategies: (i) preventing initial bacterial adhesion through passive micro/nanostructuring, superhydrophobic or superhydrophilic surfaces, and active release-based coatings; and (ii) inhibiting the proliferation and persistence of attached bacteria via contact-killing mechanisms and controlled dismantling of the extracellular polymeric substances matrix. Mechanisms and immobilization strategies of organic (e.g., antimicrobial peptides, antibiotics) and inorganic antibacterial agents (e.g., metal ions, nanoparticles) are further compared, highlighting their advantages and limitations. Finally, the translational pathway for future antibacterial implants is outlined. By bridging mechanistic insights with emerging technologies, next-generation implant surfaces may achieve durable antibacterial function, enhanced osseointegration, and improved long-term outcomes for patients at risk of peri-implantitis.